Fashion Communication Design: analysis of information consumption by Fashion Design students at a Brazilian university (ModaPalavra e-periódico, 2024)
Based on investigation in Design that develops a digital interface aimed at academic education in Fashion Design, this paper presents part of its exploratory phase. The objective of this paper is to analyze how Fashion Design students at the State University of Londrina consume Fashion content to identify opportunities for digital media to complement university education and prepare them for the professional market. The research method is based on literature review on the evolution of Fashion communication from the beginning to its current context and the application of a questionnaire with students and interviews with teachers. Answers from the first and fourth year are selected for comparison and the main comments from the interviews to support the discussion on the most important issues observed. Finally, it is discussed how communication between professors and students and the academic path can influence students’ search for fashion information. The paper results in expanding perspectives and possibilities for digital fashion communication media with educational resources that complement university education and assist students in the complex professional fashion system.
Keywords: fashion communication design; fashion digital media; fashion design education